2016
DOI: 10.1515/popore-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Recent distribution of Echinodermata species in Spitsbergen coastal waters

Abstract: Thirty-two species of echinoderms from epibenthic sledges, dredges, scuba diving, and other samples (in total: 467 samples and c. 20 000 specimens) from fjords and coastal waters off Spitsbergen were analysed between 1996 and 2014. The most numerous group of echinoderms in the coastal waters off Spitsbergen is brittle stars (78% of the total individuals). The echinoderms do not form any clear assemblages according to depth or distance from glacial sedimentation and substrate. Some species prefer hard bottom (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Furthermore, data from Wiktor et al (2022) suggests changes in the macroalgae composition in the Arctic with ongoing climate change (Wiktor et al, 2022). Three new starfish species were reported off the western coasts of Svalbard the first time: Doplopteraster multipes, Marthasterias glacialis and Asterias rubens, which had previously been reported only further south at the Norwegian coast (Deja et al, 2016).…”
Section: Range Shiftsmentioning
confidence: 92%
“…Furthermore, data from Wiktor et al (2022) suggests changes in the macroalgae composition in the Arctic with ongoing climate change (Wiktor et al, 2022). Three new starfish species were reported off the western coasts of Svalbard the first time: Doplopteraster multipes, Marthasterias glacialis and Asterias rubens, which had previously been reported only further south at the Norwegian coast (Deja et al, 2016).…”
Section: Range Shiftsmentioning
confidence: 92%
“…This level of taxonomic resolution was su cient for the distinction of both meso-scale (depth gradient) and large-scale (different fjords and bays) distribution patterns of benthic epifauna. The results have shown that the most distinct benthic community, dominated by brittle stars (most likely Ophiocten sericeum or Ophiura robusta (Deja et al 2016)), was present in Borebukta at 3-52 depths. Burgerbukta was unique for high numbers of shrimps and bryozoans Alcyonidium sp.…”
Section: What De Nes Differences Of Benthic Assemblages: Geographical...mentioning
confidence: 93%
“…This was suggested to be either due to a fluctuating slow natural range extension (Węsławski et al 2011), a single exceptional warm inflow of Atlantic water carrying larvae north (Berge et al 2005), and/or adult specimens transported to Svalbard by rafted debris or ship traffic (Węsławski and Kotwicki 2018;Leopold et al 2019). Other examples of temperate and boreal species being transported northwards with the extension of the North Atlantic Current are the euphausiid Meganyctiphanes norvegica (Buchholz et al 2010) and the starfish Asterias rubens (Deja et al 2016). The Norwegian Biodiversity Information Centre has identified 31 species to be 'doorstep species' for Svalbard.…”
Section: Introductionmentioning
confidence: 99%